Polycrystal Al2O3-TiC-diamond composite material as well as preparation method and application thereof

By introducing a TiC transition layer into the diamond composite material, strong chemical bonding is solved, and the problem of thermal cracks easily formed in traditional diamond composite sheets during high temperature and high pressure sintering is improved, and the impact resistance and thermal stability of the composite material are improved.

CN119407178APending Publication Date: 2025-02-11CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411318412.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional diamond composite sheets are prone to thermal cracks during high temperature and high pressure sintering, resulting in unstable performance and short service life. The preparation cost of polycrystalline diamonds is high, which limits its large-scale application.

Method used

Using polycrystalline Al2O3-TiC-diamond composite material, a TiC transition layer is introduced between the diamond layer and the Al2O3 layer, forming a strong chemical bond, enhancing interface strength, blocking crack propagation, thereby improving impact resistance.

Benefits of technology

The impact resistance and thermal stability of the composite material are improved, the fragmentation and layering behavior caused by low interface strength is reduced, and the overall performance of the material is better than that of commercial petroleum composite sheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407178A_ABST
    Figure CN119407178A_ABST
Patent Text Reader

Abstract

The invention relates to a polycrystalline Al2O3-TiC-diamond composite material and a preparation method and application thereof, belongs to the field of superhard materials, and discloses a polycrystalline Al2O3-TiC-diamond composite material which comprises a polycrystalline diamond layer, a polycrystalline Al2O3 layer and a polycrystalline TiC transition layer. Wherein the polycrystalline diamond layer and the polycrystalline Al2O3 layer are combined through the polycrystalline TiC transition layer. The composite material has good thermal stability and mechanical properties, can be applied to oil drilling, and has a great application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of superhard materials, and in particular to a polycrystalline Al2O3-TiC-diamond composite material and a preparation method and application thereof. Background Art

[0002] Diamond composite sheets are made by sintering diamond powder and cemented carbide base materials under ultra-high pressure and high temperature conditions. They have the high hardness, high wear resistance and thermal conductivity of diamond, and the strength and impact toughness of cemented carbide. They are ideal materials for manufacturing cutting tools, drilling bits and other wear-resistant tools. Therefore, diamond composite sheets play a vital role in the use of drill bits in the field of modern drilling. However, as the deepest drilling depth of drilling platforms at home and abroad gradually deepens, higher requirements are put forward for the performance of drill teeth used in oil and gas drilling. Therefore, it is necessary to have better performance for the diamond composite sheets on the drill bit, such as better impact strength and hardness. The traditional diamond composite sheet sintering technology is to sinter diamond powder and metal sintering aid powder evenly after mixing them under high temperature and high pressure. Due to the large difference in thermal expansion coefficients between metal sintering aids and diamonds, it is easy to cause thermal cracks to form diamond composite sheets under high temperature conditions. This not only affects the yield rate in the synthesis process of diamond composite sheets, but also affects the service life of diamond composite sheets under extreme heat conditions during use, thereby affecting the service life of the drill bit and the drilling cost. In addition, the diamond powder used to prepare polycrystalline diamond is expensive, which to some extent limits the large-scale application of polycrystalline diamond.

[0003] The interface between the diamond layer and the matrix of conventional petroleum composite sheets often becomes a weak area for crack propagation, which is prone to fracture, delamination and other behaviors under load. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the material properties of PDC tooth synthetic materials in the prior art are unstable during the high temperature and high pressure synthesis process. In the research, the applicant of the present invention proposed to compound Al2O3, TiC and polycrystalline diamond to obtain a polycrystalline Al2O3-TiC-diamond three-layer composite material, which not only has the characteristics of high hardness and high fracture toughness of the diamond layer, but the middle TiC transition layer can also be beneficial to build a strong chemical bond with the diamond layer, thereby promoting the bonding strength of the composite material layer; on the other hand, the TiC transition layer enhances the interface strength between the two, and the strong chemical bonding can hinder the crack propagation, thereby improving the impact resistance of the overall petroleum composite sheet.

[0005] Based on this, the first aspect of the present invention provides a polycrystalline Al2O3-TiC-diamond composite material, which includes a polycrystalline diamond layer, a polycrystalline Al2O3 layer and a polycrystalline TiC transition layer; wherein the polycrystalline diamond layer and the polycrystalline Al2O3 layer are combined through the polycrystalline TiC transition layer.

[0006] Alumina has good mechanical strength and high temperature stability, so it can be widely used in various fields. It can reduce internal stress cracking and increase cutting volume in the synthesis of diamond composite sheets; titanium carbide is a very hard and highly wear-resistant material, often used to manufacture high-hardness and high-wear-resistant tools and parts. The hardness of titanium carbide is second only to diamond and boron carbide, with a hardness of 1400-2000HV, and its wear resistance is 5-10 times that of cemented carbide. In addition, titanium carbide also has extremely high heat resistance, corrosion resistance, oxidation resistance and stability, and is an ideal enhancer. Therefore, in the process of manufacturing diamond drill bits, adding an appropriate amount of titanium carbide can significantly improve the hardness, wear resistance, corrosion resistance and heat resistance of the drill bit.

[0007] The composite material formed by combining the polycrystalline diamond layer and the polycrystalline Al2O3 layer through the polycrystalline TiC transition layer is composed of three materials with different physical and chemical properties. In the present invention, the materials of each layer can cooperate with each other and are independent of each other, each of which maintains its inherent physical, chemical and mechanical properties, and there is a multi-phase solid material at the interface. The various materials complement each other in performance and produce a synergistic effect, so that the comprehensive performance of the composite material is better than that of the original component materials and meets various requirements.

[0008] The second aspect of the present invention provides a method for preparing a polycrystalline Al2O3-TiC-diamond composite material, which comprises: sintering and optionally post-treating an assembly block of a diamond molded body containing diamond and optionally a sintering aid A, a polycrystalline TiC molded body containing polycrystalline TiC and optionally a sintering aid B, and a polycrystalline Al2O3 molded body containing polycrystalline Al2O3 and optionally a sintering aid C, which are assembled in sequence.

[0009] The third aspect of the present invention provides a polycrystalline Al2O3-TiC-diamond composite material prepared by the preparation method described in the second aspect of the present invention.

[0010] The fourth aspect of the present invention provides use of the polycrystalline Al2O3-TiC-diamond composite material according to the first aspect of the present invention or the third aspect of the present invention in a PDC drill bit.

[0011] Through the above technical solution, the present invention has at least the following beneficial effects compared with the prior art:

[0012] (1) The polycrystalline diamond layer and the polycrystalline Al2O3 layer in the composite material of the present invention are combined through the polycrystalline TiC transition layer, which can reduce the fragmentation and delamination of the composite material caused by low interface strength and improve the impact resistance of the composite material;

[0013] (2) The composite material of the present invention has good thermal stability and mechanical properties, and the overall performance and impact resistance of the composite material are higher than those of general commercial petroleum composite sheets;

[0014] (3) The composite material of the present invention can be used in oil drilling applications, and TiC and Al2O3 materials are easy to obtain and relatively cheap, thus having great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 In one embodiment of the present invention, polycrystalline Al2O is prepared 3- Process flow chart of TiC-diamond composite material;

[0016] Figure 2 is an apparatus diagram of a sample high temperature and high pressure assembly diagram in one embodiment of the present invention;

[0017] Figure 3 is an ultra-depth-of-field electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material of Example 1;

[0018] Figure 4 is a scanning electron microscope analysis image of a polycrystalline Al2O3 layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 1;

[0019] Figure 5 This is a scanning electron microscope analysis image of the polycrystalline TiC layer of the polycrystalline Al2O3-TiC-diamond composite material of Example 1;

[0020] Figure 6 This is a scanning electron microscope analysis image of a polycrystalline diamond layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 1;

[0021] Figure 7 This is an ultra-depth electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material of Example 2;

[0022] Figure 8 is a scanning electron microscope analysis image of a polycrystalline Al2O3 layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 2;

[0023] Fig. 9 This is a scanning electron microscope analysis image of the polycrystalline TiC layer of the polycrystalline Al2O3-TiC-diamond composite material of Example 2;

[0024] Fig.10This is a scanning electron microscope analysis image of a polycrystalline diamond layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 2;

[0025] Fig.11 is an ultra-depth-of-field electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material of Example 3;

[0026] Fig.12 is a scanning electron microscope analysis image of a polycrystalline Al2O3 layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 3;

[0027] Fig.13 is a scanning electron microscope analysis image of a polycrystalline TiC layer of a polycrystalline Al2O3-TiC-diamond composite material of Example 3;

[0028] Fig.14 This is a scanning electron microscope analysis image of the polycrystalline diamond layer of the polycrystalline Al2O3-TiC-diamond composite material of Example 3. DETAILED DESCRIPTION

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] A first aspect of the present invention provides a polycrystalline Al2O3-TiC-diamond composite material, which comprises a polycrystalline diamond layer, a polycrystalline Al2O3 layer and a polycrystalline TiC transition layer; wherein the polycrystalline diamond layer and the polycrystalline Al2O3 layer are combined via the polycrystalline TiC transition layer.

[0031] The composite material of the present invention has high temperature stability and good mechanical properties, and the polycrystalline diamond layer and the polycrystalline Al2O3 layer are combined through the polycrystalline TiC transition layer, which not only has the characteristics of high hardness and high fracture toughness of the diamond layer, but also promotes the bonding strength between the composite material layers by combining the polycrystalline diamond layer and the polycrystalline Al2O3 layer through the polycrystalline TiC transition layer; it is beneficial to hinder the crack propagation, thereby improving the thermal stability and impact resistance of the overall composite material. The hardness and fracture toughness of the polycrystalline Al2O3 layer are also significantly improved. Further, it is speculated that there is an AlTiC alloy formed between the polycrystalline Al2O3 layer and the polycrystalline TiC transition layer, which can enhance the interface strength between the two, and the strong chemical bonding hinders the crack propagation, thereby improving the impact resistance of the overall petroleum composite sheet.

[0032] The composite material of the present invention has a close bond. According to one embodiment of the present invention, the density of the composite material is not less than 98%.

[0033] The density of the composite material in the present invention is measured by using an ultra-depth electron microscope and SEM to detect the microscopic morphology of the sample. The polycrystalline material is tightly combined and has a high density. On the other hand, the density of the composite material is measured using the Archimedean principle.

[0034] According to an embodiment of the present invention, there is a chemical bond between the polycrystalline diamond layer and the polycrystalline TiC transition layer. The above embodiment enables the composite material to have better thermal stability and mechanical properties.

[0035] According to a preferred embodiment of the present invention, the chemical bond force includes a chemical bond force formed by bonding A and B, wherein A is selected from at least one of Fe, Ni and Al, and B is selected from at least one of Si, Co and Fe. The aforementioned embodiment enables the composite material to reduce the fragmentation and delamination of the petroleum composite sheet caused by low interface strength, thereby improving the overall impact resistance of the petroleum composite sheet.

[0036] In the present invention, the chemical bonding force that can be cited includes the chemical bonding force between Fe and Si, the chemical bonding force between Ni and Co, the chemical bonding force between Al and Co, the chemical bonding force between Ni and Fe, and the chemical bonding force between Al and Fe.

[0037] According to one embodiment of the present invention, the grain sizes of the polycrystalline diamond layer, polycrystalline Al2O3 layer and polycrystalline TiC transition layer are independently 3nm-500μm. The composite material in the above embodiment has uniformly distributed grain size, high temperature stability and good mechanical properties.

[0038] According to one embodiment of the present invention, the grain size of the polycrystalline diamond layer is 0.1μm-15μm, for example, 0.1μm, 0.2μm, 0.3μm, 0.5μm, 0.8μm, 1μm, 1.3μm, 1.5μm, 3μm, 4μm, 5μm, 8μm, 10μm, 11μm, 13μm, 15μm, or a range consisting of any two of the above values.

[0039] According to one embodiment of the present invention, the grain size of the polycrystalline Al2O3 layer is 3nm-100nm, for example, 3nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 100nm, or a range consisting of any two of the above values.

[0040] According to one embodiment of the present invention, the grain size of the TiC transition layer is 0.5μm-10μm, for example, 0.5μm, 0.8μm, 1μm, 1.3μm, 1.5μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, or a range consisting of any two of the above values.

[0041] According to one embodiment of the present invention, the main phase of the polycrystalline diamond layer is diamond.

[0042] According to one embodiment of the present invention, the main phase of the polycrystalline Al2O3 layer is α-Al2O3.

[0043] According to one embodiment of the present invention, the main phase of the polycrystalline TiC transition layer is cubic TiC.

[0044] The phase composition of each layer of the composite material layer in the present invention is obtained by XRD detection.

[0045] According to a preferred embodiment of the present invention, the thickness ratio of the polycrystalline diamond layer, the polycrystalline Al2O3 layer and the polycrystalline TiC transition layer is 1:(0.1-20):(0.01-10).

[0046] According to a particularly preferred embodiment of the present invention, the thickness ratio of the polycrystalline diamond layer, the polycrystalline Al2O3 layer, and the polycrystalline TiC transition layer is 1:(0.5-3):(0.1-0.2). The composite material layers of the aforementioned embodiment can better interact with each other, so that the composite material has excellent heat resistance and overall impact resistance.

[0047] According to the present invention, as long as the purpose of the present invention can be achieved, the overall thickness of the composite material and the thickness between the layers can be selected as needed. The present invention provides the following exemplary description:

[0048] According to one embodiment of the present invention, the thickness of the composite material is 0.3-30 mm.

[0049] According to one embodiment of the present invention, the thickness of the polycrystalline diamond layer is 0.1-29.7 mm.

[0050] According to one embodiment of the present invention, the thickness of the polycrystalline Al2O3 layer is 0.1-29.7 mm.

[0051] According to one embodiment of the present invention, the thickness of the polycrystalline TiC transition layer is 0.1-29.7 mm.

[0052] Further, according to one embodiment of the present invention, the thickness of the composite material is 1-30 mm.

[0053] Further, according to one embodiment of the present invention, the thickness of the polycrystalline diamond layer is 0.1-10 mm.

[0054] Further, according to one embodiment of the present invention, the thickness of the polycrystalline Al2O3 layer is 0.1-20 mm.

[0055] Further, according to an embodiment of the present invention, the thickness of the polycrystalline TiC transition layer is 0.1-10 mm.

[0056] The present invention can respectively measure the thickness of the polycrystalline diamond layer, the polycrystalline TiC transition layer, the polycrystalline Al2O3 layer and the thickness of the composite material through equipment such as an ultra-depth-of-field microscope, a scanning electron microscope and a vernier caliper.

[0057] According to one embodiment of the present invention, the Vickers hardness of the polycrystalline diamond layer is 50-85 GPa.

[0058] According to one embodiment of the present invention, the fracture toughness of the polycrystalline diamond layer is 6-15.1 MPa·m 1 / 2 .

[0059] According to one embodiment of the present invention, the Vickers hardness of the polycrystalline TiC transition layer is 14-35 GPa.

[0060] According to one embodiment of the present invention, the fracture toughness of the polycrystalline TiC transition layer is 3-8 MPa·m 1 / 2 .

[0061] According to one embodiment of the present invention, the Vickers hardness of the polycrystalline Al2O3 layer is 19-35 GPa.

[0062] According to one embodiment of the present invention, the fracture toughness of the polycrystalline Al2O3 layer is 2-4 MPa·m 1 / 2 .

[0063] The present invention tests the sample cross section and uses a Vickers hardness tester to measure the Vickers hardness and fracture toughness of the polycrystalline diamond layer, the polycrystalline TiC transition layer, and the polycrystalline Al2O3 layer. A high-hardness composite material is obtained, and the overall impact resistance of the composite material is also improved. The cumulative impact energy measured by the drop hammer impact test is 600-1500J, which is better than the control sample composite sheet, and its cumulative impact energy is about 900J.

[0064] A second aspect of the present invention provides a method for preparing a polycrystalline Al2O3-TiC-diamond composite material, the preparation method comprising:

[0065] The assembled block of a diamond molded body containing single crystal diamond and optionally sintering aid A, a polycrystalline TiC molded body containing polycrystalline TiC and optionally sintering aid B, and a polycrystalline Al2O3 molded body containing polycrystalline Al2O3 and optionally sintering aid C, which are assembled in sequence, is sintered and optionally post-treated.

[0066] In the present invention, the middle TiC layer of the Al2O3-TiC-diamond composite material prepared by the preparation method of the present invention respectively forms strong chemical bonds with the diamond layer and the Al2O3 layer, thereby reducing the fragmentation and delamination of the petroleum composite sheet caused by low interface strength, improving the overall impact resistance of the petroleum composite sheet, and making it have good thermal stability and mechanical properties.

[0067] Before sintering, the molded body can be cold pressed as needed to reduce the volume collapse of the sample. The cold pressing method is a conventional method in the art. For example, the preferred temperature for cold pressing is 20-25°C, the preferred pressure is 1-3 GPa, and the preferred holding time is 10s-120s.

[0068] The diamond molded body of the present invention can be obtained by conventional methods in the art, for example, by mixing single crystal diamond, optional sintering aid A and water and then pre-pressing and molding, wherein the amount of water used is generally in a mass ratio of (0.8-5) to the mass of the single crystal diamond:1.

[0069] The polycrystalline TiC molded body containing polycrystalline TiC and optionally sintering aid B in the present invention can be obtained according to conventional methods in the art, for example, the polycrystalline TiC and optionally sintering aid B are mixed with water and then pre-pressed, wherein the amount of water used is generally in a mass ratio of (1-30):1 to the mass ratio of single crystal diamond.

[0070] The assembled block of the polycrystalline Al2O3 molded body containing polycrystalline Al2O3 and optionally a sintering aid C in the present invention can be sintered according to conventional methods in the art, for example, the polycrystalline Al2O3 and optionally a sintering aid C are mixed with water and then pre-pressed, wherein the amount of water used is generally in a mass ratio of (1-30):1 to the mass of the single crystal diamond.

[0071] In the present invention, each of the single crystal diamond, TiC and polycrystalline Al2O3 may contain some impurities, the purity of which is generally 95-100wt%. Before using the corresponding raw materials, the raw materials can be cleaned and dried, for example, by using anhydrous ethanol for cleaning and then drying. That is, in some embodiments, the single crystal diamond, TiC and polycrystalline Al2O3 are cleaned and dried using anhydrous ethanol, and then each is independently and optionally mixed with a corresponding sintering aid.

[0072] In the present invention, single crystal diamond, TiC, and polycrystalline Al2O3 are ultimately pre-pressed to obtain corresponding molded bodies, and there is no particular limitation on their specific forms, which may be conventional block or powder forms in the art.

[0073] According to an embodiment of the present invention, the sintering conditions include: a sintering pressure of 3-25 GPa. Grain growth affects the performance and microstructure of the material, and high pressure can inhibit abnormal growth of grains under high temperature conditions.

[0074] According to one embodiment of the present invention, the sintering conditions include: a sintering temperature of 600-2000°C, preferably 1200-1600°C.

[0075] According to one embodiment of the present invention, the sintering conditions include: a holding time of 20s-4h, preferably 10-60min.

[0076] According to one embodiment of the present invention, the sintering conditions include: a holding time of 10s-20min, preferably 1-5min.

[0077] According to one embodiment of the present invention, the post-treatment method includes grinding, polishing and pickling, so as to achieve the required flatness and finish of the composite material, remove the sintering aid of the diamond layer, and improve the mechanical properties of the sample working layer.

[0078] Among them, grinding, polishing and pickling are conventional technical means in this field, and the present invention will not elaborate on them.

[0079] In order to prevent the sample from being contaminated at high temperature, according to one embodiment of the present invention, the assembly block is wrapped in a metal inclusion and calcined. The diamond molded body, the polycrystalline TiC molded body and the polycrystalline Al2O3 molded body are layered in sequence and wrapped with a metal inclusion, which can prevent the sample from being contaminated in a high temperature and high pressure environment.

[0080] In the present invention, specifically, Figure 2 As shown, in one embodiment, it is a device diagram of a sample high temperature and high pressure assembly diagram, a polycrystalline Al2O3 molded body, a polycrystalline TiC molded body and a diamond molded body are placed in a metal inclusion in sequence, the sample with the metal inclusion is loaded into a high pressure sintering unit, and then the high pressure sintering unit is placed in a synthesis cavity of a high pressure device for sintering, and finally the product is post-processed. The present invention uses a six-sided top press for high temperature and high pressure sintering, after reaching a set pressure, the temperature is increased and heated, and the temperature is kept for a period of time. After the temperature holding time is over, the heating is stopped, and the pressure is slowly reduced after the pressure is kept for 2 minutes.

[0081] According to a preferred embodiment of the present invention, Figure 1As shown, polycrystalline Al2O 3- The process flow chart of TiC-diamond composite material, the preparation method comprises: taking Al2O3, taking TiC, taking diamond powder, washing and drying them respectively, adding sintering aid C to Al2O3, adding sintering aid B to TiC, adding sintering aid A to diamond, mixing them respectively, pre-pressing and forming, vacuum drying, respectively obtaining polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding; then layering the polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding in a specific order and wrapping them with metal inclusions to pre-press and synthesize assembly block samples, grinding and polishing the metal inclusions, then degreasing, ultrasonic cleaning, vacuum drying, loading the wrapped samples into high pressure assembly sintering units, placing the sintering units into a drying oven at a constant temperature of 120°C to dry for standby use. A six-sided top press is used for high-temperature and high-pressure sintering. The sample in the synthesis cavity is then taken out and the metal wrapped around the sample is removed. The synthesized sample is subjected to post-processing such as grinding and polishing to obtain a polycrystalline Al2O3-TiC-diamond composite material. Finally, the performance of the composite material is tested.

[0082] According to one embodiment of the present invention, based on the mass of the single crystal diamond, the content of the sintering aid A is 1-20wt%.

[0083] According to one embodiment of the present invention, based on polycrystalline TiC, the content of the sintering aid B is 1-15 wt %.

[0084] According to one embodiment of the present invention, based on polycrystalline TiC, the content of the sintering aid C is 1-15wt%.

[0085] The present invention promotes the sintering densification of the composite material by adding a sintering aid and promoting the sintering densification of the composite material under a high temperature and high pressure environment, mainly by reducing the sintering activation energy, activating the lattice, destroying the stable lattice structure, generating defects or lattice distortion, thereby promoting the sintering process. The content of the polycrystalline diamond layer, the polycrystalline TiC transition layer, and the polycrystalline Al2O3 layer is adjusted within a certain range to obtain composite materials with different hardness and different fracture toughness.

[0086] According to one embodiment of the present invention, the sintering aid A is selected from one or more of Fe, Co, Ni, Si, Fe2(CO3)3, CoCO3, NiCO3, Co2SiO4, NiSiO3, Fe6N3, CoN, Ni3N and Si3N4.

[0087] According to one embodiment of the present invention, the sintering aid B is selected from one or more of Fe, Si, Ni, Al and Mo.

[0088] According to one embodiment of the present invention, the sintering aid C is selected from one or more of W, Ni, SiC, Y2O3, La2O3, TiO2, ZrO2 and CaO.

[0089] According to one embodiment of the present invention, the sintering aid A is selected from one or more of Co, Si, Fe2(CO3)3, CoCO3 and NiCO3, preferably Fe2(CO3)3. With the aforementioned embodiment, the sintering aid between the layers can form a more stable metal chemical bond, thereby reducing the fragmentation and delamination of the composite material caused by low interface strength, and improving the overall impact resistance of the composite material.

[0090] According to one embodiment of the present invention, the sintering aid B is selected from one or more of Fe, Al and Mo. With the aforementioned embodiment, the sintering aid between the layers can form a more stable metal chemical bond, thereby reducing the behaviors of the composite material such as fragmentation and delamination caused by low interface strength, and improving the overall impact resistance of the composite material.

[0091] According to one embodiment of the present invention, the sintering aid C is selected from one or more of W, Ni and CaO. With the above embodiment, the sintering aid between the layers can form a more stable metal chemical bond, thereby reducing the fragmentation and delamination of the composite material caused by low interface strength, and improving the overall impact resistance of the composite material.

[0092] According to one embodiment of the present invention, the grain size of the single crystal diamond is 3 nm-500 μm.

[0093] According to one embodiment of the present invention, the grain size of the polycrystalline TiC is 3 nm-500 μm.

[0094] According to one embodiment of the present invention, the grain size of polycrystalline Al2O3 is 3nm-500μm. The present invention needs to process the raw materials first, the single crystal diamond is a powder with a grain size of 3nm-500μm, the polycrystalline TiC is a block or powder with a grain size of 3nm~500μm, and the polycrystalline Al2O3 is a block or powder with a grain size of 3nm~500μm.

[0095] According to one embodiment of the present invention, the thickness of the diamond formed body is 0.1-10 mm.

[0096] According to one embodiment of the present invention, the thickness of the polycrystalline TiC molded body is 0.1-10 mm.

[0097] According to one embodiment of the present invention, the thickness of the polycrystalline Al2O3 molded body is 0.1-20 mm.

[0098] The present invention measures the thickness of polycrystalline diamond molded body, polycrystalline TiC molded body and polycrystalline Al2O3 molded body respectively by using ultra-depth microscope, scanning electron microscope and vernier caliper and other equipment. Reasonable thickness design can not only improve product performance and quality, but also reduce production cost and improve production efficiency.

[0099] The third aspect of the present invention provides a polycrystalline Al2O3-TiC-diamond composite material prepared by the preparation method described in the second aspect of the present invention.

[0100] The composite material prepared by the preparation method of the present invention has good thermal stability and mechanical properties, and the overall impact resistance of the composite material is higher than that of general commercial diamond composite sheets; in addition, the method of preparing the polycrystalline Al2O3-TiC-diamond composite material of the present invention can reduce the usage of the diamond layer, reduce the cost of raw materials, and realize large-scale industrial production and application.

[0101] The fourth aspect of the present invention provides use of the polycrystalline Al2O3-TiC-diamond composite material according to the first aspect or the third aspect of the present invention in a PDC drill bit.

[0102] The polycrystalline Al2O3-TiC-diamond composite material of the present invention has excellent heat resistance and impact resistance, and TiC and Al2O3 materials are easy to obtain and relatively cheap, and has great application prospects in PDC drill bits.

[0103] The present invention will be described in detail below by way of examples. In the following examples:

[0104] The impact energy parameters are measured by a drop hammer impact test method; the control product is a diamond composite sheet whose raw material is a diamond composite sheet composed of diamond micropowder and a Co-containing tungsten carbide matrix, and is a commercially available product with a company brand of 1613MJSP.

[0105] The test results of sample performance are shown in Table 1.

[0106] Example 1

[0107] Take 32g of polycrystalline Al2O3 block with a purity of 96% and an average grain size of 20nm, take 4g of polycrystalline TiC block with a purity of 98% and an average grain size of 1μm, take 30g of diamond powder with a purity of 97% and an average grain size of 1μm, treat them with 100ml, 80ml and 100ml of anhydrous ethanol respectively, pour out the waste liquid, dry them in an oven at 120℃, add 3% Y2O3 powder by mass to Al2O3, add 5% Fe powder by mass to TiC, and add 1% Fe powder by mass to diamond. 5% Si powder is used as a sintering aid. After mixing, 50ml of deionized water is added to each of them and pre-pressed and vacuum dried to obtain polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding respectively; then the polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding are layered in a specific order and wrapped with metal inclusions, the metal inclusions are ground and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120°C for standby use. High-temperature and high-pressure sintering is carried out using a six-sided top press. After reaching the set pressure of 4.5GPa, the temperature is increased and heated, and the temperature is kept at 1400°C for 25 minutes. After the insulation time is over, the heating is stopped, and the pressure is kept for 2 minutes before slowly reducing the pressure. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthetic sample is ground, polished and pickled to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0108] The ultra-depth electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material in Example 1 is as follows: Figure 3 As shown, the polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0109] Among them, the scanning electron microscope analysis images of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer are shown as follows: Figure 4 , 5 As shown in Figure 6, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 22nm, the average grain size in the polycrystalline TiC layer is 1μm, and the average grain size in the polycrystalline diamond layer is 1μm.

[0110] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0111] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 5.9mm, of which the thickness of the polycrystalline Al2O3 layer is 3.1mm, the thickness of the polycrystalline TiC layer is 0.2mm, the thickness of the polycrystalline diamond layer is 2.6mm, and the sample density is 98.5%; the Vickers hardness of the polycrystalline diamond layer is 52GPa, and the fracture toughness is 6.7MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 25GPa, and the fracture toughness is 3.0MPa·m 1 / 2 ; The Vickers hardness of the polycrystalline Al2O3 layer is 20GPa and the fracture toughness is 2.5MPa·m 1 / 2 The thermal stability temperature of the composite material is 853℃, and the cumulative impact energy is 1020J.

[0112] Example 2

[0113] Take 35g of polycrystalline Al2O3 block with a purity of 97% and an average grain size of 50nm, take 6g of polycrystalline TiC block with a purity of 97% and an average grain size of 5μm, take 44g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid and dry them in an oven at 120℃; after drying, add 5% TiO2 powder by mass to Al2O3, 3% Ni powder by mass to TiC, and 9% Ni powder by mass to diamond. % Co powder as sintering aid, each mixed and added with 60ml deionized water and pre-pressed, vacuum dried to obtain polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body, then the polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body are layered in a specific order and wrapped with metal inclusions, the metal inclusions are polished and polished, then degreased, ultrasonically cleaned, vacuum dried, the wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven at a constant temperature of 120°C for standby use. High temperature and high pressure sintering is carried out using a six-sided top press, and after reaching the set pressure of 5.5GPa, the temperature is increased and heated, and the temperature is kept at 1550°C for 15 minutes. After the insulation is completed, the heating is stopped, and the pressure is kept for 2 minutes, and then the pressure is slowly reduced. Take out the sample in the synthesis cavity, remove the metal wrapped outside the sample, and grind, polish and pickle the synthesized sample to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0114] The ultra-depth electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material in Example 2 is as follows: Figure 7 As shown, the polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0115] Among them, the scanning electron microscope analysis images of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer are shown as follows: Figure 8 , 9 As shown in Figure 10, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 62nm, the average grain size in the polycrystalline TiC layer is 5.1μm, and the average grain size in the polycrystalline diamond layer is 213nm;

[0116] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0117] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 7.1mm, of which the thickness of the polycrystalline Al2O3 layer is 3.1mm, the thickness of the polycrystalline TiC transition layer is 0.4mm, and the thickness of the polycrystalline diamond layer is 3.6mm. The sample density is 99.5%, the Vickers hardness of the polycrystalline diamond layer is 75GPa, and the fracture toughness is 11.2MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 32GPa, and the fracture toughness is 3.4MPa·m 1 / 2 The Vickers hardness of the polycrystalline Al2O3 layer is 25GPa, and the fracture toughness is 3.0MPa·m 1 / 2 The high temperature stability of the composite material is 865℃ and the cumulative impact energy is 1260J.

[0118] Example 3

[0119] Take 66g of polycrystalline Al2O3 block with a purity of 98% and an average grain size of 40nm, take 72g of polycrystalline TiC block with a purity of 98% and an average grain size of 2μm, take 75g of diamond powder with a purity of 99% and an average grain size of 10μm, treat them with 180ml, 160ml and 170ml of anhydrous ethanol respectively, pour out the waste liquid, and dry them in an oven at 120℃; after drying, add 3% CaO powder by mass to Al2O3, 5% Al powder by mass to TiC, and 5% Al powder by mass to diamond. The number of 10% Co powder is used as a sintering aid. After mixing each, 100ml of deionized water is added to pre-press and form, and vacuum drying is performed to obtain polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding respectively; then the polycrystalline Al2O3 molding, polycrystalline TiC molding and diamond molding are layered in a specific order and wrapped with metal inclusions, the metal inclusions are ground and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120℃ for standby use. High-temperature and high-pressure sintering is performed using a six-sided top press. After reaching the set pressure of 7GPa, the temperature is increased and heated, and the temperature is kept at 1300℃ for 40 minutes. After the insulation is completed, the heating is stopped, and the pressure is kept for 2 minutes before slowly reducing the pressure. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthesized sample is ground, polished and pickled to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0120] The ultra-depth electron microscope image of the polycrystalline Al2O3-TiC-diamond composite material in Example 3 is as follows: Fig.11 As shown, the polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0121] Among them, the scanning electron microscope analysis images of the polycrystalline Al2O3 layer, polycrystalline TiC layer and polycrystalline diamond layer are shown as follows: Fig.12 , 13 As shown in Figure 14, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 44nm, the average grain size in the polycrystalline TiC layer is 2μm, and the average grain size in the polycrystalline diamond layer is 10μm.

[0122] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0123] The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 20mm, of which the thickness of the polycrystalline Al2O3 layer is 6mm, the thickness of the polycrystalline TiC layer is 7mm, and the thickness of the polycrystalline diamond layer is 7mm. The sample density is 99.7%, the Vickers hardness of the polycrystalline diamond layer is 84GPa, and the fracture toughness is 13.3MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 38GPa and the fracture toughness is 4.2MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 32GPa and the fracture toughness is 3.9MPa·m 1 / 2 The high temperature stability temperature of the composite material is 956℃ and the cumulative impact energy is 1180J.

[0124] Example 4

[0125] Take 35g of polycrystalline Al2O3 block with a purity of 98% and an average grain size of 300μm, take 6g of polycrystalline TiC block with a purity of 98% and an average grain size of 300μm, take 44g of diamond powder with a purity of 99% and an average grain size of 350μm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid, and dry them in an oven at 120℃; after drying, add 3% CaO powder by mass to Al2O3, 5% Al powder by mass to TiC, and 1% Al powder by mass to diamond. 0% Co powder is used as a sintering aid, and 60ml of deionized water is added to each of them after mixing and pre-pressing, and vacuum drying is performed to obtain polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies respectively. Then, the polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are layered in a specific order and wrapped with metal inclusions, and the metal inclusions are polished and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120°C for standby use. High-temperature and high-pressure sintering is performed using a six-sided top press. After reaching a set pressure of 5.5GPa, the temperature is increased and heated, and the temperature is kept at 1550°C for 15 minutes. After the insulation is completed, the heating is stopped, and the pressure is kept for 2 minutes, and then the pressure is slowly reduced. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthetic sample is polished, polished and pickled to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0126] The polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0127] Among them, through the electron microscope scanning image analysis of the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer are all polycrystalline structures, and the average grain size in the polycrystalline Al2O3 layer is 312μm, the average grain size in the polycrystalline TiC layer is 326μm, and the average grain size in the polycrystalline diamond layer is 325μm;

[0128] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0129] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 7.3mm, of which the thickness of the polycrystalline Al2O3 layer is 3.1mm, the thickness of the polycrystalline TiC transition layer is 0.4mm, and the thickness of the polycrystalline diamond layer is 3.6mm. The sample density is 96.6%, the Vickers hardness of the polycrystalline diamond layer is 56GPa, and the fracture toughness is 8.0MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 25GPa, and the fracture toughness is 3.2MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 25GPa and the fracture toughness is 2.6MPa·m 1 / 2 The high temperature stability temperature of the composite material is 820℃ and the cumulative impact energy is 930J.

[0130] Example 5

[0131] Take 35g of polycrystalline Al2O3 block with a purity of 97% and an average grain size of 50nm, take 6g of polycrystalline TiC block with a purity of 97% and an average grain size of 5μm, take 44g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid, and dry them in an oven at 120℃; after drying, add 5% TiO2 powder by mass to Al2O3, 3% Ni powder by mass to TiC, and 16% F powder by mass to diamond respectively. e2(CO3)3 is used as a sintering aid. After mixing each, 60 ml of deionized water is added and pre-pressed. After vacuum drying, polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are obtained respectively. Then, the polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are layered in a specific order and wrapped with metal inclusions. The metal inclusions are grinded and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped samples are loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120°C for standby use. High-temperature and high-pressure sintering is carried out using a six-sided top press. After reaching the set pressure of 5.5 GPa, the temperature is increased and heated. After the insulation is completed, the heating is stopped. After the pressure is maintained for 2 minutes, the pressure is slowly reduced. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthesized sample is grinded, polished and pickled to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0132] The polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0133] Among them, through the electron microscope scanning image analysis of the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 61nm, the average grain size in the polycrystalline TiC layer is 5μm, and the average grain size in the polycrystalline diamond layer is 196nm.

[0134] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0135] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 6.9mm, of which the thickness of the polycrystalline Al2O3 layer is 3mm, the thickness of the polycrystalline TiC layer is 0.4mm, and the thickness of the polycrystalline diamond layer is 3.5mm. The sample density is 99.8%, the Vickers hardness of the polycrystalline diamond layer is 85GPa, and the fracture toughness is 14.5MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 35GPa and the fracture toughness is 5.3MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 35GPa and the fracture toughness is 4MPa·m 1 / 2 The high temperature stability temperature of the composite material is 970℃ and the cumulative impact energy is 1500J.

[0136] Example 6

[0137] Take 35g of polycrystalline Al2O3 block with a purity of 97% and an average grain size of 50nm, take 6g of polycrystalline TiC block with a purity of 97% and an average grain size of 5μm, take 22g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid, and dry them in an oven at 120℃; after drying, add 5% TiO2 powder by mass to Al2O3, 3% Ni powder by mass to TiC, and 8% Ni powder by mass to diamond. % Ni powder as sintering aid, each mixed and added with 60ml deionized water and pre-pressed, vacuum dried to obtain polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body, then the polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body are layered in a specific order and wrapped with metal inclusions, the metal inclusions are polished and polished, then degreased, ultrasonically cleaned, vacuum dried, the wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven at a constant temperature of 120°C for standby use. High temperature and high pressure sintering is carried out using a six-sided top press, and after reaching the set pressure of 5.5GPa, the temperature is increased and heated, and the temperature is kept at 1550°C for 15 minutes. After the insulation is completed, the heating is stopped, and the pressure is kept for 2 minutes, and then the pressure is slowly reduced. Take out the sample in the synthesis cavity, remove the metal wrapped outside the sample, and grind, polish and pickle the synthesized sample to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0138] The polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0139] Among them, through the electron microscope scanning image analysis of the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 61nm, the average grain size in the polycrystalline TiC layer is 5.1μm, and the average grain size in the polycrystalline diamond layer is 253nm.

[0140] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0141] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 5.5mm, of which the thickness of the polycrystalline Al2O3 layer is 3.2mm, the thickness of the polycrystalline TiC layer is 0.5mm, and the thickness of the polycrystalline diamond layer is 1.8mm. The sample density is 94.8%, the Vickers hardness of the polycrystalline diamond layer is 45GPa, and the fracture toughness is 7.5MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 18GPa and the fracture toughness is 2.5MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 15GPa and the fracture toughness is 2.3MPa·m 1 / 2 The high temperature stability temperature of the composite material is 850℃ and the cumulative impact energy is 970J.

[0142] Example 7

[0143] Take 35g of polycrystalline Al2O3 block with a purity of 97% and an average grain size of 50nm, take 6g of polycrystalline TiC block with a purity of 97% and an average grain size of 5μm, take 44g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid and dry them in an oven at 120℃; after drying, add 0.5% CaO powder by mass to Al2O3, 0.6% Al powder by mass to TiC, and 0.5% Al powder by mass to diamond. .6% Co powder is used as a sintering aid. After mixing each, 60ml of deionized water is added and pre-pressed. After vacuum drying, polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are obtained respectively. Then, the polycrystalline Al2O3 molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are layered in a specific order and wrapped with metal inclusions. The metal inclusions are grinded and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped samples are loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120°C for standby use. High-temperature and high-pressure sintering is performed using a six-sided top press. After reaching the set pressure of 5.5GPa, the temperature is increased and heated. After the insulation is completed, the heating is stopped. After the pressure is maintained for 2 minutes, the pressure is slowly reduced. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthesized sample is grinded, polished and pickled to obtain a polycrystalline Al2O3-TiC-diamond composite material.

[0144] The polycrystalline Al2O3-TiC-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, the polycrystalline TiC layer and the polycrystalline diamond layer in the polycrystalline Al2O3-TiC-diamond composite material.

[0145] Among them, through the electron microscope scanning image analysis of the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer, it can be determined that the polycrystalline Al2O3 layer, the polycrystalline TiC layer, and the polycrystalline diamond layer are all polycrystalline structures, the average grain size in the polycrystalline Al2O3 layer is 64nm, the average grain size in the polycrystalline TiC layer is 5.1μm, and the average grain size in the polycrystalline diamond layer is 236nm.

[0146] Through XRD, it is found that the main phase of the polycrystalline diamond layer is diamond, the main phase of the polycrystalline Al2O3 layer is α-Al2O3, and the main phase of the polycrystalline TiC transition layer is cubic crystal structure TiC.

[0147] Sample performance test: The thickness of the prepared polycrystalline Al2O3-TiC-diamond composite material is 7.4mm, of which the thickness of the polycrystalline Al2O3 layer is 3.2mm, the thickness of the polycrystalline TiC layer is 0.5mm, and the thickness of the polycrystalline diamond layer is 3.7mm. The sample density is 95.6%, the Vickers hardness of the polycrystalline diamond layer is 49GPa, and the fracture toughness is 6.5MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 19GPa and the fracture toughness is 2.5MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 15GPa and the fracture toughness is 1.9MPa·m 1 / 2 The high temperature stability temperature of the composite material is 650℃ and the cumulative impact energy is 600J.

[0148] Comparative Example 1

[0149] Take 35g of polycrystalline Al2O3 block with a purity of 97% and an average grain size of 50nm, take 6g of polycrystalline B4C block with a purity of 98% and an average grain size of 2μm, take 44g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid and dry them in an oven at 120℃; after drying, add 3% CaO powder by mass to Al2O3, 5% Al powder by mass to B4C, and 10% Al powder by mass to diamond. % Co powder as sintering aid, each mixed and added with 60ml deionized water and pre-pressed, vacuum dried to obtain polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body, then the polycrystalline Al2O3 molded body, polycrystalline TiC molded body and diamond molded body are layered in a specific order and wrapped with metal inclusions, the metal inclusions are polished and polished, then degreased, ultrasonically cleaned, vacuum dried, the wrapped sample is loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven at a constant temperature of 120°C for standby use. High temperature and high pressure sintering is carried out using a six-sided top press, and after reaching the set pressure of 5.5GPa, the temperature is increased and heated, and the temperature is kept at 1550°C for 15 minutes. After the insulation is completed, the heating is stopped, and the pressure is kept for 2 minutes, and then the pressure is slowly reduced. Take out the sample in the synthesis cavity, remove the metal wrapped outside the sample, and grind, polish and pickle the synthesized sample to obtain a polycrystalline Al2O3-B4C-diamond composite material.

[0150] The polycrystalline Al2O3-B4C-diamond composite material is destroyed to test the performance of the polycrystalline Al2O3 layer, polycrystalline B4C layer and polycrystalline diamond layer in the polycrystalline Al2O3-B4C-diamond composite material.

[0151] The thickness of the prepared polycrystalline Al2O3-B4C-diamond composite material is 7.2 mm, of which the thickness of the polycrystalline Al2O3 layer is 3.2 mm, the thickness of the polycrystalline B4C layer is 0.4 mm, and the thickness of the polycrystalline diamond layer is 0.6 mm. The sample density is 96.3%, the Vickers hardness of the polycrystalline diamond layer is 75 GPa, and the fracture toughness is 10.6 MPa·m 1 / 2 The Vickers hardness of the polycrystalline B4C transition layer is 20GPa and the fracture toughness is 1.5MPa·m 1 / 2 The hardness of the polycrystalline Al2O3 layer is 16GPa and the fracture toughness is 1.6MPa·m 1 / 2 The high temperature stability temperature of the composite material is 600℃ and the cumulative impact energy is 470J.

[0152] Comparative Example 2

[0153] Take 35g of polycrystalline SiC block with a purity of 98% and an average grain size of 1μm, take 6g of polycrystalline TiC block with a purity of 97% and an average grain size of 5μm, take 44g of diamond powder with a purity of 98% and an average grain size of 200nm, treat them with 85ml, 90ml and 90ml of anhydrous ethanol respectively, pour out the waste liquid and dry them in an oven at 120℃; after drying, add 5% TiO2 powder by mass to SiC, 3% Ni powder by mass to SiC, and 9% TiO2 powder by mass to diamond respectively. Co powder is used as a sintering aid. After mixing each, 60 ml of deionized water is added and pre-pressed. After vacuum drying, polycrystalline SiC molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are obtained respectively. Then, the polycrystalline SiC molded bodies, polycrystalline TiC molded bodies and diamond molded bodies are layered in a specific order and wrapped with metal inclusions. The metal inclusions are polished and polished, and then degreased, ultrasonically cleaned, and vacuum dried. The wrapped samples are loaded into a high-pressure assembly sintering unit, and the sintering unit is placed in a drying oven and dried at a constant temperature of 120 ° C for standby use. High temperature and high pressure sintering is carried out using a six-sided top press. After reaching the set pressure of 5.5 GPa, the temperature is increased and heated. After the insulation is completed, the heating is stopped. After the pressure is maintained for 2 minutes, the pressure is slowly reduced. The sample in the synthesis cavity is taken out, the metal wrapped outside the sample is removed, and the synthesized sample is polished, polished and pickled to obtain a polycrystalline SiC-TiC-diamond composite material.

[0154] The polycrystalline SiC-TiC-diamond composite material is destroyed to test the performance of the polycrystalline SiC layer, the polycrystalline TiC layer and the polycrystalline diamond layer in the polycrystalline SiC-TiC-diamond composite material.

[0155] Sample performance test: The thickness of the prepared polycrystalline SiC-TiC-diamond composite material is about 7.5mm, of which the thickness of the polycrystalline SiC layer is 3.3mm, the thickness of the polycrystalline TiC transition layer is 0.4mm, and the thickness of the polycrystalline diamond layer is 3.7mm. The sample density is 94.7%, the Vickers hardness of the polycrystalline diamond layer is 70GPa, and the fracture toughness is 9.8MPa·m 1 / 2 The Vickers hardness of the polycrystalline TiC transition layer is 30GPa and the fracture toughness is 2.9MPa·m 1 / 2 The Vickers hardness of the polycrystalline SiC layer is 20 GPa and the fracture toughness is 2.3 MPa·m 1 / 2 The high temperature stability of the composite material is 700℃ and the cumulative impact energy is 500J.

[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polycrystalline Al2O3-TiC-diamond composite material, characterized in that: The composite material comprises a polycrystalline diamond layer, a polycrystalline Al2O3 layer and a polycrystalline TiC transition layer; Wherein, the polycrystalline diamond layer and the polycrystalline Al2O3 layer are combined through the polycrystalline TiC transition layer.

2. The composite material according to claim 1, wherein The polycrystalline diamond layer and the polycrystalline TiC transition layer have a chemical bond force; and / or The density of the composite material is not less than 98%; and / or The grain sizes of the polycrystalline diamond layer, the polycrystalline Al2O3 layer and the polycrystalline TiC transition layer are independently 3nm-500μm.

3. The composite material according to claim 2, wherein: The chemical bond force includes the chemical bond force formed by the bonding of A and B, wherein: A is selected from at least one of Fe, Ni and Al, and B is selected from at least one of Si, Co and Fe; and / or The grain size of the polycrystalline diamond layer is 0.1 μm-15 μm; and / or The grain size of the polycrystalline Al2O3 layer is 3nm-100nm; and / or The grain size of the TiC transition layer is 0.5 μm-10 μm.

4. The composite material according to claim 1, wherein The main phase of the polycrystalline diamond layer is diamond; and / or The main phase of the polycrystalline Al2O3 layer is α-Al2O3; and / or The main phase of the polycrystalline TiC transition layer is cubic TiC.

5. The composite material according to any one of claims 1 to 4, wherein: The thickness ratio of the polycrystalline diamond layer, the polycrystalline Al2O3 layer and the polycrystalline TiC transition layer is 1:(0.1-20):(0.01-10); and / or The thickness of the composite material is 0.3-30 mm; and / or The thickness of the polycrystalline diamond layer is 0.1-29.7 mm; and / or The thickness of the polycrystalline Al2O3 layer is 0.1-29.7 mm; and / or The thickness of the polycrystalline TiC transition layer is 0.1-29.7 mm.

6. The composite material according to claim 5, wherein The thickness ratio of the polycrystalline diamond layer, the polycrystalline Al2O3 layer and the polycrystalline TiC transition layer is 1:(0.5-3):(0.1-0.2); and / or The thickness of the composite material is 1-30 mm; and / or The thickness of the polycrystalline diamond layer is 0.1-10 mm; and / or The thickness of the polycrystalline Al2O3 layer is 0.1-20 mm; and / or The thickness of the polycrystalline TiC transition layer is 0.1-10 mm.

7. The composite material according to any one of claims 1 to 6, wherein: The Vickers hardness of the polycrystalline diamond layer is 50-85 GPa; and / or The fracture toughness of the polycrystalline diamond layer is 6-15.1 MPa·m 1 / 2 ; and / or The Vickers hardness of the polycrystalline TiC transition layer is 14-35 GPa; and / or The fracture toughness of the polycrystalline TiC transition layer is 3-8 MPa·m 1 / 2 ; and / or The Vickers hardness of the polycrystalline Al2O3 layer is 19-35 GPa; and / or The fracture toughness of the polycrystalline Al2O3 layer is 2-4 MPa·m 1 / 2 .

8. A method for preparing a polycrystalline Al2O3-TiC-diamond composite material, characterized in that: The preparation method comprises: The assembled block of a diamond molded body containing single crystal diamond and optionally sintering aid A, a polycrystalline TiC molded body containing polycrystalline TiC and optionally sintering aid B, and a polycrystalline Al2O3 molded body containing polycrystalline Al2O3 and optionally sintering aid C, which are assembled in sequence, is sintered and optionally post-treated.

9. The preparation method according to claim 8, wherein: The sintering conditions include: The sintering pressure is 3-25 GPa; and / or The sintering temperature is 600-2000°C; and / or The holding time is 20s-4h; and / or The holding time is 10s-20min; and / or The post-processing method includes: grinding, polishing and pickling; and / or The assembly block is wrapped in a metal wrapping body and fired.

10. The preparation method according to claim 8, wherein: Based on the mass of the single crystal diamond, the content of the sintering aid A is 1-20wt%; and / or Based on polycrystalline TiC, the content of the sintering aid B is 1-15wt%; and / or Based on polycrystalline Al2O3: the content of the sintering aid C is 1-15wt%.

11. The preparation method according to claim 10, wherein: The sintering aid A is selected from one or more of Fe, Co, Ni, Si, Fe2(CO3)3, CoCO3, NiCO3, Co2SiO4, NiSiO3, Fe6N3, CoN, Ni3N and Si3N4; and / or The sintering aid B is selected from one or more of Fe, Si, Ni, Al and Mo; and / or The sintering aid C is selected from one or more of W, Ni, SiC, Y2O3, La2O3, TiO2, ZrO2 and CaO.

12. The preparation method according to claim 11, wherein The sintering aid A is selected from one or more of Co, Si, Fe2(CO3)3, CoCO3 and NiCO3; and / or The sintering aid B is selected from one or more of Fe, Al and Mo; and / or The sintering aid C is selected from one or more of W, Ni and CaO.

13. The preparation method according to any one of claims 8 to 12, wherein: The grain size of the single crystal diamond is 3nm to 500μm; and / or The grain size of the polycrystalline TiC is 3nm to 500μm; and / or The grain size of the polycrystalline Al2O3 is 3nm to 500μm; and / or The thickness of the single crystal diamond molded body is 0.1-10 mm; and / or The thickness of the polycrystalline TiC molded body is 0.1-10 mm; and / or The thickness of the polycrystalline Al2O3 molded body is 0.1-20 mm.

14. A polycrystalline Al2O3-TiC-diamond composite material prepared by the preparation method according to any one of claims 8 to 13.

15. Use of the polycrystalline Al2O3-TiC-diamond composite material according to any one of claims 1 to 7 and 14 in a PDC drill bit.